Applications of Diffractive Optical Elements for High Power Lasers - Hutfless, Joachim; Geiger, Manfred; Lang, A.; Frank, M.; et al. (Proceedings of SPIE, 1994)
Diffractive optical elements for high-power lasers offer interesting applications in addition to conventional refractive and reflective optics like lenses and mirrors. Their function is based on diffraction at small surface structures in the scale of the wavelength. This paper tries to assess realistically the application potential of diffractive optical elements for industrial high-power lasers. These are excimer lasers (λ = 193 ... 308 nm), Nd:YAG solid-state lasers (λ = 1.06 μm) and CO2 lasers (λ = 10.6 μm). After a short description of both the physical fundamentals of diffractive optical elements and their production processes this paper mainly deals with new methods of beam forming and guiding by diffractive optical elements as well as the integration of these optics into laser systems. Hereby the problems arising from high-power densities as well as the possibility of increasing the efficiency of the beam guiding system are stressed.
LFT Import::2019-07-15 (618)